2021
DOI: 10.17113/ftb.59.03.21.7087
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant, Cytotoxic and Antidiabetic Activity of Protein Hydrolysates Prepared from Chinese Pond Turtle (Chinemys reevesii)

Abstract: Research background. Cardiovascular diseases and diabetes are the biggest causes of death globally. Bioactive peptides derived from many food proteins using enzymatic proteolysis and food processing perform a positive impact on the prevention of these diseases. The bioactivity of grass turtle muscle proteins and their enzymatic hydrolysates has not received much attention, thus this study aims to investigate the antioxidant, antidiabetic, and cytotoxic activities of the enzymatic hydrolysates of grass turtle m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
6
0
2
Order By: Relevance
“…However, no significant variation was noted when the enzyme/substrate ratio was increased to 5%, which may cause enzyme aggregation, inhibit protein substrate diffusion, and finally decrease the enzymatic hydrolysis process because of the lack of catalytic sites of the targeted enzyme [ 8 ]. Serajul Islam and others found that the optimum E/S% for the flavourzyme enzyme to obtain protein hydrolysates from a Chinese pond turtle substrate was 4% [ 17 ]. Moreover, the effect of pH on the DH was studied and displayed in Figure 1 B.…”
Section: Resultsmentioning
confidence: 99%
“…However, no significant variation was noted when the enzyme/substrate ratio was increased to 5%, which may cause enzyme aggregation, inhibit protein substrate diffusion, and finally decrease the enzymatic hydrolysis process because of the lack of catalytic sites of the targeted enzyme [ 8 ]. Serajul Islam and others found that the optimum E/S% for the flavourzyme enzyme to obtain protein hydrolysates from a Chinese pond turtle substrate was 4% [ 17 ]. Moreover, the effect of pH on the DH was studied and displayed in Figure 1 B.…”
Section: Resultsmentioning
confidence: 99%
“…De acuerdo con Niño et al (2019), la actividad antioxidante está relacionada con las secuencias peptídicas que se liberan durante la hidrolisis, debido a que entre más pequeño sea el péptido mayor actividad tendrá. También su actividad biológica puede estar relacionada con la composición de aminoácidos, el grado de hidrolisis y la distribución de los péptidos donantes de electrones capaces de reaccionar con los radicales libres para así poder convertirlos en productos más estables (Islam et al, 2021). Por otro lado, en la Fig.…”
Section: Resultados Y Discusiónunclassified
“…For the parameter FRAP, there has only been one study published, which was carried out on the Chinemys reevsesii species of turtle. Islam et al [ 81 ] evaluated FRAP in muscle cells after killing the animals. The final values of FRAP were only shown in figures of evaluated absorbance (A 700nm = 0.300) in comparison with our results (297.70 µmoL Fe 2+ /g TP), and because of this it is impossible to compare these studies.…”
Section: Discussionmentioning
confidence: 99%